The fiction of health services (Colombia Medica, 2012)
What we know today as Health Services is a fiction, perhaps shaped involuntarily, but with deep health repercussions, more negative than positive. About 24 centuries ago, Asclepius god of medicine and Hygeia goddess of hygiene and health, generated a dichotomy between disease and health that remains until today. The confusing substitution of Health Services with Medical Services began by the end of the XIX century. But it was in 1948 when the so called English National Health Service became a landmark in the world and its model was adopted by many countries, having distorted the true meaning of Health Services. The consequences of this fiction have been ominous. It is necessary to call things by its name not to deceive society and to correct the serious imbalance between Medical Services and Health Services. Hygeia and Asclepius must become a brotherhood.